2018
DOI: 10.1542/neo.19-11-e664
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Feeding on Necrotizing Enterocolitis

Abstract: Despite the recognition that enteral feeding and some clinical conditions encountered during the management of prematurity may affect the development of necrotizing enterocolitis (NEC) in premature neonates, there is still significant variation in practice. Clinicians should be aware of the current evidence regarding feeding and the development of NEC in premature neonates, specifically relating to the use of breast milk, feeding when a patent ductus arteriosus is present and during its treatment, as well as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…Feeding preterm neonates is still controversial; in some cases, enteral feeding appears to protect against the onset of NEC, and in others, it promotes changes that may contribute to the disease [ 3 ], although several guidelines have been published for VLBW infants [ 3 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Feeding preterm neonates is still controversial; in some cases, enteral feeding appears to protect against the onset of NEC, and in others, it promotes changes that may contribute to the disease [ 3 ], although several guidelines have been published for VLBW infants [ 3 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite multiple studies evaluating its risk factors, the most commonly observed associations continue to be prematurity, enteral feeding, and infection [ 2 ]. Several studies have repeatedly shown that maternal milk (MM) offers a protective effect from developing NEC compared to infant formula milk (FM) [ 3 , 4 ]. Experts have recommended MM as the choice of feeding preterm infants, followed by pasteurized donor maternal milk (DM) and FM designed for preterm infants, and they have approved the use of human- or bovine-based milk fortifiers to meet their high nutrient needs [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation